2020
DOI: 10.1021/acsnano.0c05534
|View full text |Cite
|
Sign up to set email alerts
|

Near Degeneracy of Magnetic Phases in Two-Dimensional Chromium Telluride with Enhanced Perpendicular Magnetic Anisotropy

Abstract: The discovery of atomically thin van der Waals magnets (e.g., CrI3 and Cr2Ge2Te6) has triggered a renaissance in the study of two-dimensional (2D) magnetism. Most of the 2D magnetic compounds discovered so far host only one single magnetic phase unless the system is at a phase boundary. In this work, we report the near degeneracy of magnetic phases in ultrathin chromium telluride (Cr2Te3) layers with strong perpendicular magnetic anisotropy highly desired for stabilizing 2D magnetic order. Single-crystalline C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 99 publications
5
48
0
Order By: Relevance
“…Considering that the retention of the administrated N-Ex in the liver and spleen may hinder their therapeutic efficacy, we then decorated N-Ex with SPIONs by transferrin (Tf)–transferrin receptor (TfR) interaction to improve their tumor-targeting capability ( 21 , 22 ). The magnetic behavior of Tf-SPION is shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that the retention of the administrated N-Ex in the liver and spleen may hinder their therapeutic efficacy, we then decorated N-Ex with SPIONs by transferrin (Tf)–transferrin receptor (TfR) interaction to improve their tumor-targeting capability ( 21 , 22 ). The magnetic behavior of Tf-SPION is shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…The evolution of the magnetic easy-axis direction is further characterized by the temperature dependence of the magnetic moment (M-T) [44]. Fig.…”
Section: Thickness Dependence Of the Electric Transport Anisotropy In...mentioning
confidence: 99%
“…Using mechanical exfoliation techniques, a series of 2D intrinsic magnetic materials have been synthesized, including CrX 3 (X = Cl, Br, I), CrGe(Si)Te 3 , CrSBr, CrPS 4 , and MPS 3 (M = Mn, Fe, Ni). [1][2][4][5][6][7][8][9][10] Based on first-principles calculations, hundreds of 2D vdW magnets have been predicted for breakthroughs to realize controlled synthesis of 1 and 2 unit-cell CrSe and Cr 2 Te 3 by CVD growth and found these 2D ultrathin films show obvious thickness-dependent Curie temperature, the highest value is 280 K. Xu et al [36] reported that hexagonal CrTe 2 monolayer grown on bilayer graphene substrates by MBE with T C = 200 K. Zhang et al [37] reported that trigonal ultrathin Cr 2 Te 3 films are FM with T C = 195 K and exhibit strong perpendicular magnetic anisotropy with 5 × 10 6 J m −3 , and Li et al [38] prepared 2D nanosheets of α-MnSe 2 with nonstoichiometric surfaces via soft chemical etching, which were found to be a FM semiconductor with T C = 320 K. In addition, the robust FM/AFM order have also been found in 2D non-vdW CrSe 2 , Fe 7 Se 8 , Cr 5 Te 8 , FeTe, CrTe, α-MnSe 2 , and FeSe ultrathin films, their T C is up to 110, 300, 160, 220, 367, 160, and 553 K, respectively. [27,28,31,[38][39][40][41] Compared to 2D vdW magnets, 2D non-vdW ultrathin films have strong interlayer chemical bonding.…”
Section: Introductionmentioning
confidence: 99%